The practice of implementing information and communication technologies in the course of theoretical mechanics for pedagogical universities (Pedagogy of Higher and Secondary Education, 2011)
Presented by the methodical study of theoretical mechanics of the system based on technology network e-learning, as well as, respectively, yo her teaching and methodological support.
Keywords: Internet; Intranet; ICT training; e-learning tools